1988
DOI: 10.1111/j.1600-0447.1988.tb08542.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Prevalence of Psychiatric Disorders

Abstract: More than thirty studies of the prevalence of psychiatric disorders have been reported from Western countries in the last thirty years. Significant methodological advances have occurred, including sophistication of sampling techniques, improvements in caseness definitions and identification of cases, and clear definitions and specification of rules for diagnosis. The introduction of standardized diagnostic instruments for use by trained lay interviewers is expected to facilitate studies of psychiatric epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Its most obvious limitation is that prevalence of psychiatric disorders was not estimated with a validated questionnaire: the questions were designed based on standard diagnostic categories for psychiatric disorders. However, the estimates are not independent of the reliability and validity of the methods used to determine a particular disorder's presence or absence (28,32). Although the prevalence estimates that we report may represent significant symptoms rather than the actual disorder, the estimates are nevertheless broadly consistent with previous studies.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Its most obvious limitation is that prevalence of psychiatric disorders was not estimated with a validated questionnaire: the questions were designed based on standard diagnostic categories for psychiatric disorders. However, the estimates are not independent of the reliability and validity of the methods used to determine a particular disorder's presence or absence (28,32). Although the prevalence estimates that we report may represent significant symptoms rather than the actual disorder, the estimates are nevertheless broadly consistent with previous studies.…”
Section: Discussionsupporting
confidence: 69%
“…Few studies have examined the lifetime estimates for AN and BN. The Edmonton study looked only at AN and found a lifetime prevalence rate of only 0.1% (28). The 12-month prevalence rate for BN was estimated at 1.0% in Ontario women participating in the Mental Health Supplement of the Ontario Health Survey, but results for AN were not reported (8).…”
Section: Discussionmentioning
confidence: 99%
“…Epide~nn®logY Results from epidemiological studies of mental health and psychiatric disorders in Sweden (Hagnell, 1986(Hagnell, , 1989(Hagnell, , 1990Halldin, 1984;Socialstyrelsen, 1991;SCB, 1988/89) show similar results to international findings (Regier, 1988;Bland, 1988;Bland at 1988a,b;Lehtinen & Joukamaa, 1987;I_,ehtinen et al 1990a,b;Blazer et al 1988;Henderson, 1979;Brown et al 1977;Bebbington et czl. 1981;Dilling, 1989).…”
Section: Providersmentioning
confidence: 70%
“…reviewed the prevalence of depressive disorders in this context and found that the morbid risk (for industrialised countries) for bipolar disorder was of the order of 0.24% to 0.88%. These rates have been largely unaltered by data from subsequent studies (Robins et al, 1984;Bland et al, 1988) although the Epidemiological Catchment Area (ECA) study quotes rates as high as 1.2% (Weissman et al, 1988). In the same review, incidence rates ranged from 9.2 to 15.2 new cases per 100,000 per year for men and 7.4 to 32.5 new cases per 100,000 per year for women.…”
Section: Sex Differences In Rates Of Bipolar Disordermentioning
confidence: 99%
“…Despite some suggestions that there are sex differences in both unipolar and bipolar disorder associated with genetic abnormalities linked to female chromosomes (Gershon and Bunney, 1976;Winokur and Tanna, 1969), the general consensus is that the female to male/sex ratio for rates of bipolar disorder is in the range 1: 1.2 to 1.3: 1 with non-significant sex differences Robins et al, 1984;Bland et al, 1988) and, since 1981, interest in sex differences has focused on unipolar depression. Sex differences in rates of unipolar depression also considered studies of non-bipolar or unipolar depression to that time.…”
Section: Sex Differences In Rates Of Bipolar Disordermentioning
confidence: 99%